Analysis of Deep Learning Approach in Grade 8 Mathematics Textbook on Statistics - Dewi, Rivani Adistia; Juandi, Dadang; Turmudi, Turmudi (Jurnal Pendidikan Progresif, 2025)
Analysis of Deep Learning Approach in Grade 8 Mathematics Textbook on Statistics. The deep learning approach is considered strategic to answer the challenges of 21st century education, especially in developing students' critical and creative thinking skills. This study aims to analyze the extent to which the principles of the deep learning approach are reflected in a grade 8 mathematics textbook, especially in statistics. The method used is content analysis of a grade 8 mathematics textbook from the Merdeka Curriculum, with indicators compiled based on the principles of the deep learning approach from the Ministry of Education and Culture, namely mindful learning, meaningful learning, and joyful learning. This instrument has been validated by experts and tested for reliability through the intra-rater reliability technique. The results showed that 9 out of 15 indicators were met, so the percentage of eligibility was 60%. The book’s strengths lie in its mindful learning and joyful learning aspects, which are reflected in the presentation of concepts with more than one method and not dogmatic, the use of diverse visual and contextual approaches, as well as fun activities and building students' confidence. However, meaningful learning aspects such as integration between subjects and the use of digital technology are still minimal. These findings indicate the need to strengthen the content of the book through the insertion of open-ended questions, collaborative activities, and exploratory projects to realize a full deep learning approach. This study recommends the development of more exploratory, contextual, and transdisciplinary textbooks as learning instruments. Keywords: deep learning, statistics, textbook analysis.